Occurrence, prevalence and viral load of deformed wing virus variants in Apis mellifera colonies in Chile. Issue 1 (1st January 2020) - Riveros, Gustavo; Arismendi, Nolberto; Zapata, Nelson; Evans, David; Pérez, Ivonne; Aldea, Patricia; Vargas, Marisol
Abstract : Deformed wing virus (DWV) is one of the most common viruses in apiaries worldwide, and its presence in Chilean apiaries is no exception. There are three well-defined master variants described as DWV-A, DWV-B (or VDV-1) and DWV-C. We studied the prevalence, load and recombinant genotypes among DWV variants in honey bees from Chilean apiaries. We also compared the viral load in each region in colonies that were treated or untreated against Varroa destructor . Using real-time PCR with specific primers enabled us to determine that DWV-A was the most prevalent (71%) throughout Chile, with a higher level than DWV-B (circa 3% prevalence), and almost 60-times more load, especially in northern Chile. The viral load was lower only in treated colonies located in the Metropolitana, Biobío/Ñuble and Los Ríos regions. The DWV-C genotype and recombinants were not detected. This suggests that viral recombinant events are limited since DWV-B is still uncommon in honey bee hives at present. This is the first study involving DWV-B in Chile.